Differential Utilization of Palliative Care Consultation Between Medical and Surgical Services. (April 2020) - Nguyen, Minh-Thuy; Feeney, Timothy; Kim, Chanmin; Drake, F. Thurston; Mitchell, Suzanne E.; Bednarczyk, Magdalena; Sanchez, Sabrina E.
There is a paucity of data regarding the utilization of palliative care consultation (PCC) in surgical specialties. We conducted a retrospective review of 2321 adult patients (age ≥18) who died within 6 months of admission to Boston Medical Center from 2012 to 2017. Patients were included for analysis if their length of stay was more than 48 hours and if, based on their diagnoses as determined by literature review and expert consensus, they would have benefited from PCC. Bayesian regression was used to estimate the odds ratio (OR) and 99% credible intervals (CrI) of receiving PCC adjusted for age, sex, race, insurance status, median income, and comorbidity status. Among the 739 patients who fit the inclusion criteria, only 30% (n = 222) received PCC even though 664 (90%) and 75 (10%) of these patients were identified as warranting PCC on medical and surgical services, respectively. Of the 222 patients who received PCC, 214 (96%) were cared for by medical services and 8 (4%) were cared for by surgical services. Patients cared for primarily by surgical were significantly less likely to receive PCC than primary patients of medical service providers (OR, 0.19, 99% CrI, 0.056-0.48). At our institution, many surgical patients appropriate for PCC are unable to benefit from this service due to low consultation numbers. Further investigation is warranted to examine if this phenomenon is observed at other institutions, elucidate the reasons for this disparity, and develop interventions to increase the appropriate use of PCC throughout all medical specialties.